The Oyster Mushroom Business Development Strategy In Anduonohu Sub-District Poasia District Kendari City - Aynul Izati; Ilma Sarimustaqiyma Rianse; Samsul Alam Fyka (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
The purpose of this study was to determine the development of the oyster mushroom business in Anduonohu ​​Village, Poasia District, Kendari City. This research was conducted in June 2022. The object of this research was Tiga Putra Fram's oyster mushroom business. The method used is the case study method. The analysis used was SWOT analysis. The results showed that the strategy for developing an oyster mushroom business in Anduonohu ​​Village, Poasia District, Kendari City that could be applied was the SO strategy: increasing product sales volume by optimizing promotions through online media and offline media, opening cooperation with other parties related to the increase in soft skills and processed oyster mushrooms. ST Strategy: Implement a pricing strategy to maintain customer loyalty and improve the quality of the oyster mushroom products produced. WT's strategy: increasing cooperation between the government, white oyster mushroom entrepreneurs, and raw material suppliers related to oyster mushroom business policies and utilizing people's purchasing power by holding promotions.